2017
DOI: 10.3390/app7090876
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Electroencephalographic Activity in Response to the Earthy Odorants Geosmin and 2-Methylisoborneol

Abstract: Geosmin and 2-methylisoborneol, molecules with the same odor characteristics, are mainly responsible for the smell of soil and cause odor problems worldwide in drinking water supplies. However, the effect of these odor molecules on human brain function is still unclear. The present investigation aimed to evaluate the effect of inhalation of geosmin and 2-methylisoborneol on human electroencephalographic (EEG) activity in order to understand whether their action on brain wave activity is the same or different. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 45 publications
0
16
1
Order By: Relevance
“…According to our previous studies, women highly responded well to aroma components than men. 17,19,21,38,39 In contrast, men are highly sensitive to black pepper essential oil than women in this study.…”
Section: F I G U R Econtrasting
confidence: 55%
See 4 more Smart Citations
“…According to our previous studies, women highly responded well to aroma components than men. 17,19,21,38,39 In contrast, men are highly sensitive to black pepper essential oil than women in this study.…”
Section: F I G U R Econtrasting
confidence: 55%
“…When compared with men, women are highly sensitive to both compounds. 17 In another study, molecules with the same odor characteristics (geosmin and 2-methylisoborneol) are also exhibited markedly different EEG activity in men and women 21 . It was also found that gender variation occurred in the EEG activity of resting, stimulus, and non-stimulus conditions.…”
Section: F I G U R Ementioning
confidence: 95%
See 3 more Smart Citations